Therapeutic Responses of Imatinib and Nilotinib among CML Patients in Hasan Sadikin Hospital Bandung - Sumantri, Agung Firmansyah; Oehadian, Amaylia; Wijaya, Indra; Vidyaniati, Putri; Rahmaniati, Rahmaniati (Indonesian Journal of Cancer, 2018)
Introduction: Chronic Myeloid Leukemia (CML) is a myeloproliferative malignancy with an estimated incidence in the world of 1-2 cases per 100,000 adults. The use of Tyrosine Kinase Inhibitors (TKI) as a therapy for CML is still the first choice for treatment, but some cases show a high level of resistance or intolerance to TKI therapy. This study aims to identify the therapeutic responses of imatinib and nilotinib among CML patients in Bandung.Method: This study is an analytical descriptive study of CML patients at Hasan Sadikin Hospital’s Hematology and Medical Oncology Outpatient Clinic in 2017. The total number of samples in this study is 244 patients, consisting of 199 patients with Imatinib therapy and 45 patients with Nilotinib therapy. The data is processed using SPSS Statistics 22.0 software.Result: The results showed that CML patients had a median age of 42 years, sex ratio of 1: 1 and the highest prevalence was in Bandung City (21.3%). Hematologic response is dominated by complete hematologic response, as high as 72.86% with Imatinib and 66.67% with Nilotinib. Molecular response 3-6 months post therapy is dominated by suboptimal response in as many as 36,8% with Imatinib and failure in as many as 50% with Nilotinib. Molecular response 12-18 months post therapy is dominated by failure in as high as 69,4% with Imatinib and 52,4% with Nilotinib.Conclusion: Based on the molecular response, the rates of suboptimal response and resistance are quite high. Regular monitoring standards of therapy for CML patients are needed to identify TKI resistance so alternative therapies can be provided to improve the outcomes.